Use of multicriteria decision analysis for assessing the benefit and risk of over‐the‐counter analgesics. (13th July 2017) - Moore, Andrew; Crossley, Anne; Ng, Bernard; Phillips, Lawrence; Sancak, Özgür; Rainsford, K.D.
Abstract: Objectives: To test the ability of a multicriteria decision analysis (MCDA) model to incorporate disparate data sources of varying quality along with clinical judgement in a benefit–risk assessment of six well‐known pain‐relief drugs. Methods: Six over‐the‐counter (OTC) analgesics were evaluated against three favourable effects and eight unfavourable effects by seven experts who specialise in the relief of pain, two in a 2‐day facilitated workshop whose input data and judgements were later peer‐reviewed by five additional experts. Key findings: Ibuprofen salts and solubilised emerged with the best benefit–risk profile, followed by naproxen, ibuprofen acid, diclofenac, paracetamol and aspirin. Conclusions: Multicriteria decision analysis enabled participants to evaluate the OTC analgesics against a range of favourable and unfavourable effects in a group setting that enabled all issues to be openly aired and debated. The model was easily communicated and understood by the peer reviewers, so the model should be comprehensible to physicians, pharmacists and other health professionals.